Qualitative assessment of patients’ attitudes and expectations toward BCIs and implications for future technology development - Schicktanz, Silke; Amelung, Till; Rieger, Jochem W. (Frontiers in Systems Neuroscience, 2015)
Brain-Computer-Interfaces (BCIs) are important for the next generation of neuro-prosthesis innovations. Only few pilot projects have tested patients’ abilities to control BCIs as well as their satisfaction with the offered technologies. On the one hand, little is known about patients’ moral attitudes towards the benefit-risk-ratio of BCIs as well as their needs, priorities, and expectations. On the other hand, ethics experts intensively discuss the general risks of BCIs as well as the limits of neuro-enhancement. To our knowledge, we present here the first qualitative interview study with ten chronic patients matching the potential user categories for motor and communication BCIs to assess their practical and moral attitudes towards this technology. The interviews reveal practical and moral attitudes towards motor BCIs that can impact future technology development. We discuss our empirical findings on patients’ perspectives and compare them to neuroscientists’ and ethicists’ perspectives. This analysis indicates only partial overlap between the potential users’ and the experts’ assessments of BCI-technology. It points out the importance of considering the needs and desires of the targeted patient group. Based on our findings, we suggest a multi-fold approach to the development of clinical BCIs, rooted in the participatory technology-development. We conclude that clinical BCI development needs to be explored in a disease-related and culturally sensitive way.